PENDAMPINGAN DAN PEMBINAAN SARANA PENGOLAHAN USAHA PETERNAKAN KAMBING PE DI DISTRIK AIMAS, KABUPATEN SORONG: Assistance and Training of PE Goat Processing Facilities in Aimas District of Sorong - Muhammad Djunaidi; Trisiwi Widayati; Gino N. Cepeda; Tatak Reko Purwanto; Freddy Pattiselanno (IGKOJEI: Jurnal Pengabdian Masyarakat, 2022)
ABSTRACT  The Ettawah Crossbreed Goat (PE) as a type of small ruminant has several advantages because it is a dual purpose type, which is capable of producing meat and milk. The "Guidance for Improvement of Agricultural Product Processing Facilities" from the Ministry of Agriculture through the Department of Animal Husbandry and Animal Health of West Papua Province, mandates the activities of PE Goat Farming Business Assistance and Development of Processing Facilities Development in Aimas District, Sorong Regency. The activity is carried out by the Department of Animal Husbandry, Faculty of Animal Husbandry, University of Papua in Manokwari. Respondents are PE goat breeders from farmer groups Setia Kawan, Margo Tani and Margo Utomo in Aimas District, they are assisted by the Animal Husbandry and Veteriner Service of West Papua Province. The success of a good PE goat agribusiness is indicated by the better linkage (network) between related aspects from upstream to downstream. In the development of PE goat agribusiness in Aimas, Sorong, three types (levels) of business, namely: 1) production level, 2) processing level and 3) marketing level need to be developed synchronously to achieve optimal results.  Keywords: COVID-19;  Participatory Rural Appraisal; Vaccination    ABSTRAK  Kambing Peranakan Ettawah (PE) sebagai salah satu jenis ruminansia kecil memiliki beberapa keunggulan karena merupakan tipe dual purposes yang mampu menghasilkan daging dan susu. Program “Pembinaan Perbaikan Sarana Pengolahan Hasil Pertanian” dari Departemen Pertanian melalui Dinas Peternakan dan Kesehatan Hewan Provinsi Papua Barat, mengamanatkan kegiatan Pendampingan Usaha Peternakan Kambing PE dan Pembinaan Pengembangan Sarana Pengolahan di Distrik Aimas Kabupaten Sorong.  Pelaksana kegiatan adalah Jurusan Paternakan Fakultas Peternakan Universitas Papua di Manokwari dan sebagai responden adalah peternak kambing PE dari kelompok tani Setia Kawan, Margo Tani dan Margo Utomo di Distrik Aimas sebagai peternak binaan Dinas Peternakan dan Kesehatan Hewan Provinsi Papua Barat. Keberhasilan agribisnis kambing PE yang baik diindikasikan dengan semakin baiknya jalinan (jaringan) antar aspek-aspek terkait mulai dari hulu sampai dengan hilir.  Dalam pengembangan agribisnis kambing PE di Aimas, Sorong, tiga macam (tingkat) usaha yaitu: 1) tingkat produksi, 2) tingkat pengolahan dan 3) tingkat pemasaran perlu dikembangkan secara sinkron untuk mencapai hasil yang optimal.  Kata kunci: Aimas; Kambing PE; Peternakan; Sorong.